Health and sustainability of glaciers in High Mountain Asia - Evan Miles (Nature Portfolio, 2021)
Glaciers in High Mountain Asia are a key water resource. The authors use remote sensing data and a regional implementation of the continuity equation to quantify glacier ablation and accumulation rates for 2000–2016, and establish current climatic-geometric imbalances that imply strong reductions in ice volume by 2100.